Sequential extraction protocol for bio-calcium from saltwater crocodile (Crocodylus porosus) bone: Physicochemical and molecular studies - Yarnpakdee, Suthasinee; Senphan, Theeraphol; Benjakul, Soottawat; Sriket, Chodsana (My University, 2026)
Saltwater crocodile ( Crocodylus porosus ; SC) farming generates 45% bone waste, creating environmental challenges but also representing an underutilized source of calcium. This study presents the first comprehensive protocol for extracting bio-calcium from SC bone through sequential processing: autoclaving, alkaline soaking, ethanol extraction, and hydrogen peroxide bleaching. The extraction process yielded 16.94% bio-calcium with a high mineral density (26.37% Ca and 13.83% P) and an average particle size of 6.77 μm. XRD confirmed the preserved hydroxyapatite structure, while FTIR revealed the complete elimination of the organic matrix in the resulting bio-calcium. SEM-EDS demonstrated uniform elemental distribution with no detectable heavy metals. Remarkably, in vitro calcium bioavailability reached 15.24%, representing a 78% enhancement over fish bone bio-calcium and doubling synthetic supplement performance. Preserved collagen-derived amino acids facilitate calcium-peptide chelation, explaining the superior absorption. The developed valorization process converts aquaculture waste into high-value ingredients with potential applications in food and pharmaceuticals.
Keywords: Aquaculture byproducts; Bio-calcium; Bioavailability; Hydroxyapatite; Saltwater crocodile bone; Waste valorization